Protective effect of antirheumatic drugs on dementia in rheumatoid arthritis patients - Judge, AD; Garriga-Fuentes, C; Arden, NK; Lovestone, S; Prieto-Alhambra, D; Cooper, C; Edwards, CJ (Elsevier, 2017)
INTRODUCTION Rheumatoid Arthritis is a systemic inflammatory disease and classical disease-modifying anti-rheumatic drugs (cDMARDs) have proven efficacy. It is unknown what impact cDMARDs might have on dementia as an outcome. METHODS Incident diagnoses of Rheumatoid Arthritis in persons over 18 years from 1995 to 2011 were identified from the UK Clinical Practice Research Datalink. 3,876 cDMARD users were propensity score matched to 1,938 non-users, on a wide range of confounders. Impact on dementia was assessed using survival models. RESULTS cDMARD users were at reduced risk of dementia (hazard ratio: 0.60; 95% confidence intervals: 0.42-0.85). The effect was strongest in Methotrexate users (0.52; 0.34-0.82). DISCUSSION The strong effect of cDMARD use on a halving of dementia risk requires replication in a trial and may provide an important therapeutic pharmacological treatment.